2022
DOI: 10.2196/41891
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of e–Mental Health Interventions for Informal Caregivers of Adults With Chronic Diseases: Mixed Methods Systematic Review With a Qualitative Comparative Analysis and Thematic Synthesis

Abstract: Background Informal caregivers commonly experience mental health difficulties related to their caregiving role. e–Mental health interventions provide mental health support in a format that may be more accessible to informal caregivers. However, e–mental health interventions are seldom implemented in real-world practice. Objective This mixed methods systematic review aimed to examine factors associated with the effectiveness and implementation of e–menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 157 publications
1
7
0
Order By: Relevance
“…Interventions can also be designed to provide caregivers with empathy and understanding by tailoring interventions to caregiver characteristics (e.g., cultural background) and caring situations (e.g., stage of care recipient’s CKD, treatment modality) to develop content that reflects caregivers’ lived experiences [ 57 ]. Tailoring has been found to enhance the relevance and acceptability of interventions for caregivers of people living with CKD and caregivers of people living with other health conditions [ 1 , 77 81 ]. Additionally, tailoring interventions based on caregiver’s cultural background may enhance intervention effectiveness [ 82 , 83 ], and has been found to improve the acceptability of interventions for caregivers in other settings [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions can also be designed to provide caregivers with empathy and understanding by tailoring interventions to caregiver characteristics (e.g., cultural background) and caring situations (e.g., stage of care recipient’s CKD, treatment modality) to develop content that reflects caregivers’ lived experiences [ 57 ]. Tailoring has been found to enhance the relevance and acceptability of interventions for caregivers of people living with CKD and caregivers of people living with other health conditions [ 1 , 77 81 ]. Additionally, tailoring interventions based on caregiver’s cultural background may enhance intervention effectiveness [ 82 , 83 ], and has been found to improve the acceptability of interventions for caregivers in other settings [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study identified several implementation factors within all domains of the CFIR that require consideration during the design and implementation of an e–mental health intervention for caregivers of people living with CKD. Some identified factors align with existing caregiving literature that has similarly identified the relative advantage of e–mental health interventions (eg, flexible access), the barriers caregivers may experience if accessing an e–mental health intervention (eg, low digital literacy and low motivation), the presence of both positive (eg, beneficial for caregivers) and negative (eg, impersonal) views of e–mental health interventions, and the importance of designing e–mental health interventions that are easy to use and contain tailored content [ 10 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of 12 eHealth and e–mental health interventions developed for caregivers of people with dementia indicated interventions were generally not implementation ready , with little information available concerning important factors required for implementation, such as staffing and training resources [ 9 ]. A recent systematic review of the implementation of e–mental health interventions for caregivers of adults with chronic diseases identified that factors related to the implementation setting and wider context (eg, available resources, relative priority of the intervention, and external policies) have been largely neglected [ 10 ]. In addition, professionals (eg, potential implementers) were seldom engaged in understanding how interventions would fit within the current health care practice [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations